Apoptosis-associated speck-like protein containing a caspase-1 recruitment domain (ASC) contributes to osteoblast differentiation and osteogenesis - Sartoretto, Suelen; Gemini-Piperni, Sara; da Silva, Rodrigo A. [UNESP]; Calasans, Monica D.; Rucci, Nadia; Pires dos Santos, Thais M.; Lima, Inayá B. C.; Rossi, Alexandre M.; Alves, Gutemberg; Granjeiro, José M.; Teti, Anna; Zambuzzi, Willian F. [UNESP] (Wiley, 2018)
The role of apoptosis-associated speck-like protein containing a caspase-1 recruitment domain (ASC) in bone healing remains to be understood. To address this issue, we investigated the requirement of inflammasome-related genes in response to bone morphogenetic protein 7 (BMP7)-induced osteoblast differentiation in vitro. To validate the importance of ASC on osteogenesis, we subjected wild-type (WT) and ASC knockout C57BL/6 mice (ASC KO) to tibia defect to evaluate the bone healing process (up to 28 days). Our in vitro data showed that there is an involvement of ASC during BMP7-induced osteoblast differentiation, concomitant to osteogenic biomarker expression. Indeed, primary osteogenic cells from ASC KO presented a lower osteogenic profile than those obtained from WT mice. To validate this hypothesis, we evaluated the bone healing process of tibia defects on both WT and ASC KO mice genotypes and the ASC KO mice were not able to fully heal tibia defects up to 28 days, whereas WT tibia defects presented a higher bone de novo volume at this stage, evidencing ASC as an important molecule during osteogenic phenotype. In addition, we have shown a higher involvement of runt-related transcription factor 2 in WT sections during bone repair, as well as circulating bone alkaline phosphatase isoform when both were compared with ASC KO mice behavior. Altogether, our results showed for the first time the involvement of inflammasome during osteoblast differentiation and osteogenesis, which opens new avenues to understand the pathways involved in bone healing.
Keywords: ASC; bone formation; inflammasome; osteoblast; osteogenesis; regenerative medicine